(untitled) (Journal of Musikot Campus, 2025)
Curriculum development is a complex and dynamic process influenced by multiple factors including philosophy, psychology, socio-cultural context, and the nature of knowledge required by contemporary society. This article explores these broad influences in the context of Nepal’s educational system, highlighting how philosophical traditions such as perennialism, essentialism, progressivism, and others shape curricular aims and content. Psychological considerations emphasize learner needs and developmental readiness, while socio-cultural factors ensure relevance and inclusiveness in a diverse society. The evolving demands of knowledge further necessitate continuous curricular adaptations to meet global and local challenges. Understanding these interrelated factors provides critical insights for policymakers and educators aiming to design effective, responsive curricula that address both individual and societal educational goals in Nepal.